PEMETAAN KECERDASAN INTERPERSONAL ANAK TAMAN KANAK-KANAK KURNIA SALAM KECAMATAN SIAK HULU KABUPATEN KAMPAR - Widya Waroka Fatmala Ningsih; Wusono Indarto; Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract : Interpersonal intelligence one’s ability to understand feeling of others, mood, intent and one’s skills in building relationship. Phenomenon seen in the kindergarten Kurnia Salam Siak Hulu Sub-districk KamparRegency including (1) Children are afraid to interact with others (2) Son always pulled out when meeting with peers (3) Children are always attached to the teachers at the school did not want to play with friends. Research purpose for can how the child’s interpersonal intelligence. Types of research is descriptive research. Data collection using observation. Sample in the research 50 children of 25 man and 25 woman. Based on the result of data analysis, average interpersonal intelligence mapping child as 67.8% categorized quite. It’s the mean children understand feeling of others, mood, and intent in building relationship. Thus it can be concluded interpersonal intelligence Kindergarten Kurnia Salam Sub-districk Siak Hulu Regency Kampar is quite.Key words : Interpersonal intelligence, Early childhood